A taxonomic revision of the South Indian species of Curcuma Linn. (Zingiberaceae) - Mangaly , Jose K.; Sabu, M. (Rheedea, 1993)
The genus Curcuma Linn. in South India is revised. There are. in all, 17 species falling under two Viz. subgenera, subgen. Eucurcuma Schum. and subgen. Hitcheniopsis (Baker) Schum. The latter, characterised by unspurred anther lobes, is represented by a single species, C. ecalcarata. Artificial keys for the identification of the taxa, their descriptions, illustrations and other relevant notes are provided here. A new species, C. haritha is also describ,d.